The Palgrave international handbook on adult and life-long education and learning - Milana, Marcella (Palgrave Macmillan, 2017)
This Handbook provides a wide-ranging frame of reference for researching adult and lifelong education and learning. With contributions from scores of established and newer scholars from six continents, the volume covers a diverse range of geopolitical and social territories across the world.